ANALISIS PERAN KEPEMIMPINAN DALAM MENINGKATKAN KINERJA KARYAWAN DI DE’TUIK RESTO & WEDDING VENUE ANALYSIS OF THE ROLE OF LEADERSHIP IN IMPROVING EMPLOYEE PERFORMANCE AT DE'TUIK RESTO & WEDDING VENUE - Nursari, Dessy; Marselina, Resya Dwi (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
This study aims to analyze the role of leadership in improving employee performance at De’tuik Resto & Wedding Venue. Using a qualitative approach with descriptive analysis methods, this study collected data through observation, interviews, and documentation. The results of the study indicate that leadership at De’tuik Resto & Wedding Venue has a significant role in building work discipline, motivation, and team effectiveness. The participatory leadership implemented allows for more open communication, so that employees feel more appreciated and motivated to increase productivity. In addition, factors such as granting authority, clear division of tasks, and consistent guidance also contribute to improving employee performance. However, there are several challenges that still need to be overcome, such as variations in the level of initiative between employees and the effectiveness of leader communication in conveying new policies. Overall, the leadership implemented at De’tuik Resto & Wedding Venue has had a positive impact on employee performance.